High temperature resistance of self-compacting lightweight mortar incorporating expanded perlite and pumice - Karatas, Mehmet; Balunb, Bilal; Benli, Ahmet (Techno-Press, 2017)
This paper presents the effect of aggregate type on high temperature resistance of self -compacting mortars (SCM) produced with normal and lightweight aggregates like expanded perlite and pumice. Silica fume (SF) and fly ash (FA) were used as mineral additives. Totally 13 different mixtures were designed according to the aggregate rates. Mini slump flow, mini V funnel and viscometer tests were carried out on the fresh mortar. On the other hand, bulk density, porosity, water absorption and high temperature tests were made on the hardened SCM. After being heated to temperatures of 300, 600 and 900 degrees C, respectively, the tensile strength in bending and compressive strength of mortars determined. As a result of the experiments, the increase in the use of lightweight aggregate increased total water absorption and porosity of mortars. It is observed that, the increment in the usage of lightweight aggregate decreased tensile strength in bending and compressive strengths of mortar specimens exposed to high temperatures but the usage of up to 10% expanded perlite in mortar increased the compressive strength of specimens exposed to 300 degrees C.
Keywords: self-compacting lightweight mortar; lightweight aggregate; high temperature; porosity; water absorption